Percutaneous radiologic gastrostomy in patients with failed percutaneous endoscopic gastrostomy - Tang-fei Lee; Young Jong Cho; Ji Hoon Shin; Heung Kyu Ko; Jihong Park; Soo Hwan Kim; Jin-Hyoung Kim; Ho-Young Song (Gastrointestinal Intervention, 2017)
Background : To determine the technical feasibility and success rate of percutaneous radiologic gastrostomy (PRG) after failure of percutaneous endoscopic gastrostomy (PEG).